2017
DOI: 10.18203/2394-6040.ijcmph20170259
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional study of epidemiological determinants correlated with prevalence of hypertension among municipal school teachers located in suburban area

Abstract: Background: Hypertension is a major long-term health condition and is the leading cause of premature deaths among persons experiencing sedentary urban life style behaviors such as high calorie diet, lack of physical exercise and job stress. The objectives of the present study was to determine prevalence & various risk factors of hypertension among municipal school teachers in an urban slum.  Methods:The study area was a field practice area of tertiary care hospital in a metropolitan city. Municipal school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…This study finding disagreed with that recorded in Nigeria, significant sex differences was established in blood pressure distribution and agreed with the study of Vyas et al and Girish B et al in India showed that female school teachers were hypertensive by 70.9% and 72.8% respectively. 20,25,26 Also different with that found in India by Sania et al, the prevalence of HTN was higher (64%) among male teachers. This study finding showed consistent results between income and HTN from many low and middle income countries.…”
Section: Discussionmentioning
confidence: 80%
“…This study finding disagreed with that recorded in Nigeria, significant sex differences was established in blood pressure distribution and agreed with the study of Vyas et al and Girish B et al in India showed that female school teachers were hypertensive by 70.9% and 72.8% respectively. 20,25,26 Also different with that found in India by Sania et al, the prevalence of HTN was higher (64%) among male teachers. This study finding showed consistent results between income and HTN from many low and middle income countries.…”
Section: Discussionmentioning
confidence: 80%
“…This study finding disagreed with that recorded in Nigeria, significant sex differences was established in blood pressure distribution 15 and agreed with the study of Vyas et al and Girish B et al in India showed that female school teachers were hypertensive by 70.9% and 72.8% respectively. 20,21 Also different with that found in India by Sania et al, the prevalence of HTN was higher (64%) among male teachers. 22 Majority teachers (52%) were in the middle income category earning between 20,000 and 50,000 Bangladeshi Taka per month and about 61.6% had service duration more than fifteen years (Table 1).…”
Section: Discussionmentioning
confidence: 70%
“…11 In a cross sectional study of epidemiological determinants correlated with prevalence of hypertension among municipal school teachers located in suburban area, the prevalence of hypertension was 20%. 12 In a study by regarding metabolic syndrome among secondary school teachers: exploring the ignored dimension of school health programme, the prevalence of hypertension was found as 47.7%. 7 Study participants who had stress as a problem had highest prevalence of hypertension (84.6%) and lowest among those in whom stress is not a problem (24%).…”
Section: Discussionmentioning
confidence: 99%